2012
DOI: 10.1542/peds.2011-1548
|View full text |Cite
|
Sign up to set email alerts
|

Maternal HIV Infection and Vertical Transmission of Pathogenic Bacteria

Abstract: Maternal HIV infection was not associated with increased risk of maternal bacterial colonization, vertical transmission, EOS, or LOS. HIV-infected neonates, however, were at increased risk of EOS and LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Cutland et al performed the largest study published so far including more than 5000 pregnant women, of which 1347 were HIV-infected pregnant women in South Africa. This study found a significantly lower prevalence of GBS carriage in HIV-infected compared to HIV-uninfected pregnant women (17 vs. 23%; P  = 0.0002) (24). …”
Section: Maternal Gbs Colonization In Hiv-infected Pregnant Womenmentioning
confidence: 72%
See 1 more Smart Citation
“…Cutland et al performed the largest study published so far including more than 5000 pregnant women, of which 1347 were HIV-infected pregnant women in South Africa. This study found a significantly lower prevalence of GBS carriage in HIV-infected compared to HIV-uninfected pregnant women (17 vs. 23%; P  = 0.0002) (24). …”
Section: Maternal Gbs Colonization In Hiv-infected Pregnant Womenmentioning
confidence: 72%
“…On the other hand, HIV-infected women with low CD4 cell count are known to have increased prevalence of bacterial vaginosis that could compete with GBS and are more likely to take cotrimoxazole prophylaxis resulting in lower GBS carriage rates (2729). In the Cutland et al’s study, CD4 cell count was only available in a limited proportion of HIV-infected women but the majority had a CD4 count >350/mm 3 (24). …”
Section: Maternal Gbs Colonization In Hiv-infected Pregnant Womenmentioning
confidence: 99%
“…Previously reported conflicting findings,17,18 may depend on the frequency of antimicrobial use (and provision of anti-retroviral therapy). In contrast, neonatal GBS disease is increased with HIV-exposure,40 with reduced maternal GBS capsular antibody in HIV-1 infection,41,42 and/or because, as shown here, the most virulent clone, CC17, is more frequently found in HIV-infected GBS colonised women, compared to other non-CC17 types.…”
Section: Discussionmentioning
confidence: 95%
“…Data from sSA are limited, but are also conflicting for potentially important risk factors such as HIV-infection. In South Africa, maternal GBS colonisation was lower in HIV-infected mothers17 but in Malawi, only amongst HIV-infected mothers with lower CD4 counts 18. In the USA15 and Zimbabwe19 no association with HIV was found.…”
Section: Introductionmentioning
confidence: 93%
“…Extrapolating from studies in endemic settings, they may translate into an increased susceptibility to infectious diseases. HEU infants born to severely immunocompromised mothers (CD4 < 200 cells/mm 3 ) in a South African cohort were found to be at higher risk of developing early- and late-onset sepsis than those born to mothers with CD4 > 350 cells/mm 3 [49]. Data from the Ban trial in Malawi further demonstrated that low total white blood cell counts at birth are a significant predictor of serious morbidity and mortality among HEU infants [50].…”
Section: Discussionmentioning
confidence: 99%